Low velocity impact sandwich structure bamboo for aerospace applications - Md. Shah, Ain Umara (2018)
Abundant sources of bamboo in Malaysia, if fully utilized, can increase its commercial value especially in developing greener composites. In this study, material characterizations on bamboo based composites, from Malaysian species of Bambusa vulgaris, were carried out by aiming on the low velocity impact properties. Bamboo powder, as the raw material in composites, was selfprocessed through a combination of manual and machining methods. Four different loadings of bamboo powder, which ranged from 500μm to 1mm in size, consisting of 0%, 10%, 20%, and 30% by weight were applied in the preparation of the composites. Woven glass fibre type E600, embedded at the outermost top and bottom layer of composites, was used as the main reinforcement with epoxy as the polymer matrix. Sandwich structured composites were fabricated through a combination of manual hand lay-up and compression moulding techniques. From the tensile testing and scanning electron microscopy images, poor bamboo-epoxy interfacial bonding lowered the strength of the composites as the fibre loading increased. However, the highest percentage of 30% loading suggested good stress transfer in composites through observation of the peak of the Tan δ curve through dynamic mechanical analysis. For both thermal degradation and water absorption properties, the addition of bamboo fibres lowers the thermal stability and enhances the water absorption respectively, which are the drawbacks of using natural fibres. Inconsistent damage propagations were observed on the non-hybrid bamboo composites after low velocity impact due to short size bamboo fibres aligned in random orientation within the epoxy matrix. However, the impact resistance increased as the bamboo fibre loading increased. The inclusion of woven glass fibres at the top and bottom layer of the composites significantly improved the impact resistance as these layers slowed down the penetration of the impactor, thus reducing the severity of the damages. Generally, the newly developed sandwich structured bamboo filled glass-epoxy hybrid composites have potential to be used in aerospace applications with low velocity impact properties.